Clinical and prognostic role of annexin A2 in multiple myeloma. - Seckinger, Anja; Meißner, Tobias; Hillengaß, Jens; Hose, Katja; Jauch, Anna; Ewerbeck, Volker; Goldschmidt, Hartmut; Hose, Dirk (Blood, 2012)
Annexin A2 (ANXA2) promotes myeloma cell growth, reduces apoptosis in myeloma cell lines, and increases osteoclast formation. ANXA2 has been described in small cohorts of samples as expressed by myeloma cells and cells of the BM microenvironment. To investigate its clinical role, we assessed 1148 samples including independent cohorts of 332 and 701 CD138-purified myeloma cell samples from previously untreated patients together with clinical prognostic factors, chromosomal aberrations, and gene expression-based high-risk scores, along with expression of ANXA2 in whole BM samples, stromal cells, osteoblasts, osteoclasts, and BM sera. ANXA2 is expressed in all normal and malignant plasma cell samples. Higher ANXA2 expression in myeloma cells is associated with significantly inferior event-free and overall survival independently of conventional prognostic factors and is associated with gene expression-determined high risk and high proliferation. Within the BM, all cell populations, including osteoblasts, osteoclasts, and stromal cells, express ANXA2. ANXA2 expression is increased significantly in myelomatous versus normal BM serum. ANXA2 exemplifies an interesting class of targetable bone-remodeling factors expressed by normal and malignant plasma cells and the BM microenvironment that have a significant impact on survival of myeloma patients.